Effects of dopamine and domperidone on ventilation during isocapnic hypoxia in humans. - Bascom, D; Clement, I; Dorrington, K; Robbins, P (1991)
In order to investigate the role of dopamine in the ventilatory response to sustained, isocapnic hypoxia six subjects were studied three times in each of three pharmacological conditions: (1) in the absence of any drug administration, (2) during i.v. infusion of dopamine (3 micrograms.kg-1.min-1), and (3) after pretreatment with domperidone. Otherwise the experimental protocol was identical on each day and consisted of holding the subjects' end-tidal PO2 at 100 Torr for 10 min, then 50 Torr for 20 min and finally at 100 Torr again for 5 min. End-tidal PCO2 was held constant 2-3 Torr above normal throughout the experiment. Domperidone increased, and dopamine decreased the magnitudes of both the fast on- and off-responses, but neither drug affected the magnitude of the hypoxic ventilatory decline (HVD). The results of this study suggests: (1) that a peripheral dopaminergic mechanism is not involved in the genesis of HVD, and (2) the peripheral chemoreflex may be modulated peripherally to produce HVD.